CINEMATHERAPY THROUGH K-DRAMA DURING THE EARLYPERIOD OF COVID-19 PANDEMIC IN INDONESIA - Rastati, Ranny (UI Scholars Hub, 2023)
This article discusses Korean drama (K-Drama) consumption as cinematherapy during the early period of the COVID-19 pandemic in Indonesia. In cinematherapy, videos and films are considered capable of providing therapeutic and healing effects to provide a stimulus for the audience. The cinematherapy concept was introduced by Linda Berg-Cross, Pamela Jennings, and Rhoda Baruch in 1990. The problem is, in the popularity of K-Wave, can K-Drama become cinematherapy for Indonesian audiences, especially during times of crisis such as the COVID-19 pandemic? The study uses the qualitative method with online in-depth interviews and literature study. The results showed that K-Drama has the potency to be a cinematherapy for female informants because it releases stress, tension, and anxiety due to the pandemic. However, K-Drama is just entertainment for male informants since they do not watch it very often compared to female informants. Another interesting finding is that female informants favored the thriller because it provides a sensation of tension and adrenaline rush to relieve anxiety from the burdens of life during the pandemic. K-Drama is a pleasant activity to kill time during quarantine and social restrictions. The practical implication of this study is how K-Drama can be a cinematherapy for audiences to reduce tension during the early days of the COVID-19 pandemic. K-Drama can be an educational, training, and mental health tool for further research.